1980
DOI: 10.3109/03009748009112347
|View full text |Cite
|
Sign up to set email alerts
|

Is generalized Joint Laxity a Factor in Spondylolisthesis?

Abstract: A postal questionnaire designed to assess joint laxity was sent to 364 specialist female teachers of physical education who had participated in a radiological survey on the lumbar spine. 295 replied and in this group the prevalence of spondylolisthesis was 4%. Although statistical analysis failed to demonstrate a significant association between generalized joint laxity, measured with a simple scoring system, and radiological spondylolisthesis, spondylolisthesis was found to correlate with known associations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Most of the patients in spondylolisthesis group were women. In cases such as, pregnancy, general joint laxity and oophorectomy, women's vulnerability to spondylolisthesis have been reported to be increased [4,14,28].…”
Section: Discussionmentioning
confidence: 97%
“…Most of the patients in spondylolisthesis group were women. In cases such as, pregnancy, general joint laxity and oophorectomy, women's vulnerability to spondylolisthesis have been reported to be increased [4,14,28].…”
Section: Discussionmentioning
confidence: 97%
“…In a cross-sectional epidemiological survey of more than 4,000 patients, Jacobsen et al [ 54 ] found the prevalence in men is 2.7 % and the prevalence in women is 8.4 %. The increased prevalence in women may be due to an elevated expression of estrogen receptors in the facet joints cartilage [ 55 ]; alternatively, other authors have postulated that the increased prevalence in females may be due to an increased ligamentous laxity [ 56 ]. Race also affects the prevalence, however unlike in isthmic spondylolisthesis, it is more common in patients of African decent than patients of European decent [ 53 ].…”
Section: Sva<50mmmentioning
confidence: 83%
“…4 Previous studies have indicated that the condition occurs four times more frequently in women and is most commonly seen at L4 -L5. Pregnancy, 7 generalized joint laxity, 5,6 and oophorectomy 8 are thought to be predisposing factors of the condition and its predominance in women. Pregnancy, 7 generalized joint laxity, 5,6 and oophorectomy 8 are thought to be predisposing factors of the condition and its predominance in women.…”
Section: Pathophysiologymentioning
confidence: 99%